The Business Model of Digital Labour Platforms and the Income of Platform Workers in Poland: Theory and Practice - Tusińska, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The article examines the business model of digital labour platforms (DLPs) and the relative financial attractiveness of this form of work for platform workers. Research Design & Methods: The leading research methods used in the article include a critical analysis of the scientific achievements of Polish and international literature on the topic and a diagnostic survey using a questionnaire. Findings: The business model of digital labour platforms inherently exerts downward pressure on earnings, favouring low worker income. This pattern affects the pricing of both online and offline services. However, survey results indicate that most service providers in Poland have experienced an income increase since starting work through these online platforms, compared to their previous earnings. Implications / Recommendations: The business model of digital labour platforms theoretically incorporates elements that force down the incomes of service providers. However, the delivery of services within this framework can, depending on the national context, potentially lead to an increase in platform workers’ earnings. That being said, the relative income growth observed in the Polish labour market does not necessarily contradict the overarching trend of relatively low earnings for the workers in this sector. Contribution: The topic of platform work and the income of individuals engaged with DLPs in Poland have received limited attention from researchers. There has been also a notable absence of studies addressing these phenomena, particularly with regard to changes in income. The contribution of the present study is that it fills this gap in the literature.